The Water and the Heating System in the Bath of Manol Household in Söke, Aydın - Elif Gürsoy (Art-Sanat)
Besides the importance attached to bathing and building baths since the Ancient Period. While the bathing activity was being carried out in both the bazaar baths and private baths, various units within the household were being created. Besides the use of household baths in the residence, it is also known that some custom-designed various of bathing spaces were also existing in the rooms. These sections exhibit two different uses, with their functions as both a closet for placing the belongings and a spot for having a bath. It does not additionally include its water and heating system and it is only designed with a simple assembly that provides the flow of the water that is used for bathing. The bathing place that constitutes the subject of this study, is located in the Manol House which is located in the Söke District of Aydın, and it was encountered in the restoration works carried out in 2020. Within the study, the Manol House bath is introduced with visual data, and information about the water and heating system in household baths is presented. While the connection of the bath with the kitchen points to an application that we start to witness together with the examples of the ancient period, detailed information about water and heating system can also be reached. While there are traces of the usage of boiler and tap in the water system, we come across a fire chamber, a hotspot, and a chimney in the heating system.